Trisubstituted purine inhibitors of PDGFRα and their antileukemic activity in the human eosinophilic cell line EOL-1 - Malínková, Veronika; Řezníčková, Eva; Jorda, Radek; Gucký, Tomáš; Kryštof, Vladimír (Bioorganic & medicinal chemistry, 2017)
Inhibition of protein kinases is a validated concept for pharmacological intervention in cancers. Many kinase inhibitors have been approved for clinical use, but their practical application is often limited. Here, we describe a collection of 23 novel 2,6,9-trisubstituted purine derivatives with nanomolar inhibitory activities against PDGFRα, a receptor tyrosine kinase often found constitutively activated in various tumours. The compounds demonstrated strong and selective cytotoxicity in the human eosinophilic leukemia cell line EOL-1, whereas several other cell lines were substantially less sensitive. The cytotoxicity in EOL-1, which is known to express the FIP1L1-PDGFRA fusion gene encoding an oncogenic kinase, correlated significantly with PDGFRα inhibition. EOL-1 cells treated with the compounds also exhibited dose-dependent inhibition of PDGFRα autophosphorylation and suppression of its downstream signaling pathways with concomitant G1 phase arrest, confirming the proposed mechanism of action. Our results show that substituted purines can be used as platforms for preparing tyrosine kinase inhibitors with specific activity towards eosinophilic leukemia.
Keywords: Drug Screening Assays, Antitumor; Humans; inhibitory proteinkinas; Tumor Cells, Cultured; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Dose-Response Relationship, Drug; Antineoplastic Agents; Purines; Receptor, Platelet-Derived Growth Factor alpha; lidé; růstový faktor odvozený z trombocytů - receptor alfa; proliferace buněk; molekulární struktura; nádorové buňky kultivované; Molecular Structure; Protein Kinase Inhibitors; Cell Proliferation; puriny; screeningové testy protinádorových léčiv; protinádorové látky; vztah mezi dávkou a účinkem léčiva